Public Image: Aesthetic-Political Spectrums of the Image [Imagen Pública: Espectros Estético-Políticos de la Imagen] - Arancibia-Carrizo, J (Pontificia Universidad Catolica de Chile 1, 2020)
Several contemporary analyses postulate a change in the representational regime over “the public sphere” -destitution of lógos through the irruption of the image. Given this diagnosis, we suggest addressing the premature existence of a visual regime that is constitutive of the public field. There it is composed a regime of images that expresses the conditions of visibility and the grammars of the civic order which diagram the birth of the city and the “political community”. This research report postulates the need to undertake a “visual archaeology of the public sphere” that notices the historical, figurative and performative density of an incipient configuration of the “public image” and the visual order of “the public sphere”. © Instituto de Estética - Pontificia Universidad Católica de Chile